ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA YAYASAN SAHABAT BUNDA KOTA MAKASSAR - Kaharuddin, Kaharuddin (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2020)
Analysis of factors that influence employee performance at the Sahabat Bunda Makassar Foundation. The research objective is to find out the most dominant factor affecting employee performance in the data collection method used in the study is the questionnaire method, while the analysis method uses factor analysis. The factor analysis used is exploratory factor analysis. Exploratory factor analysis or principal component analysis is a factor analysis technique in which several factors will be formed in the form of latent or determinant variables that cannot be determined before the analysis is carried out. The results show that of the twenty seven measured variables, it can be concluded that up to five dominant factors can affect employee performance at the Makassar Sahabat Bunda Foundation.